High potential food wastes: Evaluation of melon seeds as spreadable butter - Sahin, Ecenur; Erem, Erenay; Guzey, Melihanur; Kesen, Minem Sena; Icyer, Necattin Cihat; Ozmen, Duygu; Toker, Omer Said; Cakmak, Hulya (WILEY, 2022)
In this study, the evaluation of the use of melon seeds, which is an important waste in domestic and industrial production, as a source and ingredient for the production of spreadable butter was investigated. After the cleaning, roasting and grinding processes applied to the melon seeds, different amounts (10% and 20% sugar, glucose and honey) of were added during the sweetening phase. Physical, chemical and texture analyzes were performed for melon butter. According to the results obtained, the highest hardness (3124.76 g) and work of shear (1405.33 gs) values were obtained in the mixtures using Glucose(20). The lowest hardness values were obtained in Sugar(10) (261.61 g) and Honey(10) (202.53 g) mixtures, which were not statistically different, and the lowest work of shear values were obtained in sugar and honey products. Considering the results, it was concluded that Sugar(10) is the most suitable for the production of melon butter production. Practical applications Among the main objectives of the study was the introduction of a new type of seed butter that was healthy and non-allergenic to the industry with evaluating food waste. The spreadable butter samples produced with this study, in which the nutritional and technological properties of melon seeds were evaluated, are a major proof that melon seeds should considered be important ingredient for food industry.
Keywords: COLOR; QUALITY; TEXTURE; Food Science & Technology